REVIEW: MAPEAMENTO QUANTITATIVO E QUALITATIVO - Francisco Benitez Baratto , Pablo; PAOLA SILVA FUCHS , JÉSSICA; LUÍZA BEUTER BARATTO , NATÁLIA; MOMBACH NYSTROM , JÚLIA; CASSIO DE BONE , YAN (Salão do Conhecimento, 2021)
Trabalho de Pesquisa realizado na Universidade Federal do Pampa